Integrated approach to managing hypertension, diabetes, and reduced GLS: a case study of ayurvedic panchakarma therapies and lifestyle modification - Thilakan, Kavitha; Kulthe, Nilesh; Ghadigaonkar, Pravin (International Journal of Research in Medical Sciences, 2024)
Hypertension, diabetes mellitus, and reduced GLS Score are prevalent cardiovascular conditions posing significant health risks. Conventional treatments often fall short in managing these conditions comprehensively, necessitating exploration of alternative approaches. This case study examines the efficacy of Ayurvedic Panchakarma therapies and lifestyle modifications in managing hypertension, diabetes, and reduced GLS Score. A 62-year-old male with hypertension, diabetes, and hypothyroidism, unresponsive to conventional medications, underwent a 7-month treatment regimen. The intervention included Panchakarma treatments and a gobipi diet box, characterized by low carbohydrates and fats, high protein, and rich potassium, along with a 1000-calorie per day diet. It is showed that the diet led to significant improvements: hypertension was reversed, weight was reduced, and lipid profiles improved. The patient’s glucose tolerance test (GTT) turned negative, indicating diabetes reversal. The comprehensive approach also addressed metabolic syndrome components, including dyslipidemia and thyroid dysfunction. Ayurvedic treatments proved effective in managing the patient’s cardiovascular conditions. Weight loss and hypertension correction contributed to significant cardiac improvements, including enhanced GLS. Additionally, the normalization of diabetes and thyroid levels, along with improved lipid profiles, underscored the efficacy of integrating Panchakarma therapies with lifestyle modifications for comprehensive cardiovascular health management.